Mechanism of allergic rhinitis treated by Centipeda minima from different geographic areas - Yanzhuo Jia; Junbo Zou; Yao Wang; Xiaofei Zhang; Yajun Shi; Yulin Liang; Dongyan Guo; Ming Yang (Taylor & Francis Group, 2021)
Context The coriander plant Centipeda minima (L.) A. Braun et Aschers (Compositae) is used for the treatment of allergic rhinitis. Objective Analyze the difference of the C. minima volatile oil from 7 geographic areas and its therapeutic effect on allergic rhinitis. Materials and methods The volatile oils from different geographic areas were extracted and analyzed, the protein and biological pathway for the treatment of allergic rhinitis were predicted by network pharmacology. Established three groups of Sprague-Dawley rat allergic rhinitis models (n = 10). The treatment group was given 100 μL/nostril of 0.1% C. minima volatile oil, the blank and model groups were given the same amount of normal saline. After 15 days, serum inflammatory factors were detected by ELISA. Nasal mucosa tissues were examined by hematoxylineosin staining and immunuhistrochemistry. Results There are differences in the content of volatile oil in the seven geographic areas. Experiments showed that the concentration of TNF-α in the serum of the administration group decreased from 63.66 ± 2.06 to 51.01 ± 4.10 (pg/mL), IL-4 decreased from 41.90 ± 3.90 to 28.68 ± 3.39 (pg/mL), IgE decreased from 22.18 ± 1.40 to 17.59 ± 1.60 (pg/mL), IL-2 increased from 314.14 ± 10.32 to 355.90 ± 10.01(pg/mL). Immunohistochemistry showed that compared with the model group, the PTGS2 and MAPK3 proteins in the administration group were significantly reduced. Discussion and conclusions C. minima volatile oil is a multi-target and multi-pathway in the treatment of allergic rhinitis, which provides a new research basis and reference for the treatment of allergic rhinitis.